'Star men' in English convict prisons, 1879-1948 - Bethell, Ben (Abingdon, Oxon ; New York, NY : Routledge, 2022)
"This book tells the story of the star class, a segregated division for first offenders in English convict prisons; known informally as 'star men', convicts assigned to the division were identified by a red star sewn to their uniforms. 'Star Men' in English Convict Prisons, 1863-1948 investigates the origins of the star class in the years leading up to its establishment in 1879, and charts its subsequent development during the late-Victorian, Edwardian and interwar decades. To what extent did the star class serve to shield 'gentleman convicts' from their social inferiors and allow them a measure of privilege? What was the precise nature of the 'contamination' by which they and other 'accidental criminals' were believed to be threatened? And why, for the first twenty years of its existence, were first offenders convicted of 'unnatural crimes' barred from the division? To explore these questions, the book considers the making and implementation of penal policy by senior civil servants and prison administrators, and the daily life and work of prisoners at policy's receiving end. It re-examines evolving notions of criminality, the competing aims of reformation and deterrence, and the role and changing nature of prison labour. Along the way, readers will encounter an array of star men, including arsonists, abortionists, sex offenders and reprieved murderers, disgraced bankers, light-fingered postmen, bent solicitors and perjuring policemen. Taking a fresh look at English prison history through converging lenses of class, sexuality, and labour, 'Star Men' in English Convict Prisons, 1863-1948 will be of great interest to penal historians and historical criminologists, and to scholars working on related aspects of modern British history"--
Contamination in English convict prison before 1879 -- 'Gentleman convicts' and 'accidental criminals' -- The convict star class: selection and formation, 1879-c.1885 -- The convict star class: accommodation and labour, 1879-1909 -- Maidstone convict prison, 1909-c.1930 -- Star men, c.1920-1948.
OCLC-licensed vendor bibliographic record.
Keywords: Prisoners -- England -- History -- 19th century; Prisoners -- England -- History -- 20th century; Prisoners -- Classification -- History -- 19th century; Prisoners -- Classification -- History -- 20th century; Prisons -- England -- History -- 19th century; SOCIAL SCIENCE / Penology; HISTORY / Europe / Great Britain